The Effect of Computer- Assisted Concept Mapping Technique on Learners' Vocabulary Retention and Autonomy Education - I. Alizadeh (Fanāvarī-i āmūzish, 2013)
Abstract: The main goal of this study was to investigate the role of computer-assisted concept mapping technique in improving learners’ autonomy and vocabulary retention. To this aim, different concepts along with related words to each concept were selected. Then, a general English test was administered as the pretest of the study and 28 learners falling within ± 1 SD were selected and were randomly assigned into two groups: control and experimental. Then, vocabulary items were taught to the groups based on two different teaching processes. The teaching process consisted of two phases for the experimental group. In the first phase, learners were to fill in the blanks in the concept mapping diagram with the target words of the study. In the second phase, learners were solicited to expand the diagram until they reach the main concepts or target words. Afterward, the learners were asked to exchange their diagrams with their peers via hyper-terminal program. On the other hand, vocabulary items were taught to the control group conventionally that is, by providing antonyms and synonyms. After the treatment period, immediate and delayed post-tests were administered to both groups. To analyze the collected data and to compare the performance of the two groups on the immediate and delayed post-tests, independent t-tests were run. Subsequently, an interview was done with the subjects in the experimental group to elicit their opinion about the computer–assisted concept mapping technique. The findings of the study showed that employing computer assisted concept mapping technique had affected learners’ autonomy and vocabulary retention positively. Moreover, the results of the interview signaled learners’ satisfaction with the technique.